О магнитоакустических свойствах биологической среды - Бондаренко, И. С. (Харьков: АНПРЭ, ХНУРЭ, Издательство «Точка», 2017)
Biological substance (blood, muscles) has electrical conductivity. Electrical field is formed in the substance at its movement into direct magnetic field. Application of acoustic emanation for themovement is studied here. Formulas for calculation of electrical field value have been obtained. Application of the results for biophysical investigations is discussed.
Keywords: излучение акустическое, оценка, скорость перемещения, напряженность